THE EFFECT OF THE IMPLEMENTATION OF LEARNING MEDIA BASED ON INTERACTIVE MULTIMEDIA ON THE LEARNING OUTCOMES MATHEMATICS OF STUDENTS IN JUNIOR HIGH SCHOOL - Ririn Febriyanti; Billy Prasetyo (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2020)
Learning media is an intermediary. The media or technology used in the learning process must be able to implement an effective communication process. The media must also be able to improve student learning outcomes. The purpose of this study was to determine whether there is an effect of student learning outcomes on mathematics after using interactive multimedia-based learning media. This research uses quantitative research methods with quasi experimental design and nonequivalent control group design. This research carried out using interactive multimedia-based learning media. From the data of this study, the SPSS output shows that the Sig. value of Independent Sample T-Test obtained 0.029. Means Sig. (2-tailed) <α that is 0.029 <0.05. To support this result, then look at the average value in the two classes. The average score of the experimental class is 73.06 and the control class average score 60. From these data, it can be seen that the mathematics learning outcomes of students using interactive multimedia-based learning media are higher than learning outcome student mathematics without using interactive multimedia-based learning media.